2023
DOI: 10.1093/bioadv/vbad040
|View full text |Cite
|
Sign up to set email alerts
|

TB-ML—a framework for comparing machine learning approaches to predict drug resistance ofMycobacterium tuberculosis

Abstract: Motivation Machine learning (ML) has shown impressive performance in predicting antimicrobial resistance (AMR) from sequence data, including for Mycobacterium tuberculosis, the causative agent of tuberculosis. However, current ML development and publication practices make it difficult for researchers and clinicians to use, test, or reproduce published models. Results We packaged a number of published and unpublished ML models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The review of the state of the art reveals a significant gap in advanced studies on drug resistance, with minimal usage of ML, as indicated by the references [16] [14] [17]. In light of this issue, the significance of this paper is underscored by the development of a predictive model designed to forecast the clinical outcomes related to TB drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The review of the state of the art reveals a significant gap in advanced studies on drug resistance, with minimal usage of ML, as indicated by the references [16] [14] [17]. In light of this issue, the significance of this paper is underscored by the development of a predictive model designed to forecast the clinical outcomes related to TB drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning has been used for detecting resistance in Mtb data as well, employing different ML methods and achieved area under ROC curve values up to 0.95 in a classification task for resistance towards selected drugs using features from 23 selected target genes known to be implicated in resistance development (22). A recent computational framework, TB-ML, provides implementations for different ML methods such are random forest, direct association and convolutional neural networks (23). Training datasets for these methods can be found in public resources, such as, for example, the PATRIC database (24).…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches for detecting resistance in Mtb employed different ML models and achieved area under ROC curve values up to 0.95 in a classification task for resistance towards selected drugs using features from 23 selected target genes known to be implicated in resistance development [26,27]. A recent computational framework, TB-ML, provides implementations for different ML methods such are random forest, direct association and convolutional neural networks [28]. Treesist-TB, a customized decision tree-based machine learning algorithm for predicting resistance in Mtb, aims to extract genomic variants which might have been missed because of overfitting problems of the standard machine learning algorithms [29].…”
Section: Introductionmentioning
confidence: 99%